2023
DOI: 10.4269/ajtmh.22-0448
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of SARS-CoV-2 IgM and IgG Antibodies 3 Months after COVID-19 Onset in Moroccan Patients

Abstract: Coronavirus disease (COVID-19) caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) poses serious global public health problems. Characterization of the immune response, particularly antibodies to SARS-CoV-2, is important for establishing vaccine strategies. The purpose of this study was to evaluate longitudinally the kinetics of anti-SARS-CoV-2 antibodies against spike protein (S1) for up to 3 months in a cohort of 169 COVID-19 patients. We enrolled COVID-19 patients at two regional hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In our study, we did not confirm an association between gender type and the prevalence of antibodies, which is also consistent with the results of the study by Assaid et al (7).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In our study, we did not confirm an association between gender type and the prevalence of antibodies, which is also consistent with the results of the study by Assaid et al (7).…”
Section: Discussionsupporting
confidence: 90%
“…The study by Assaid et al monitored by ELISA (enzyme-linked immunosorbent assay) the appearance of IgG and IgM antibodies at 3 months after the onset of COVID-19. In their study (7), they showed that IgG antibodies appeared between 2 weeks and one month after the onset of infection, persisted for 3 months in 79% of the probands studied, and then gradually decreased in levels. In contrast, 19% of probands had declining IgM antibodies after the first month of symptom onset.…”
Section: Discussionmentioning
confidence: 95%
“…In general, IgA and IgM antibodies are generated earlier than IgG isotypes, with earlier detection of IgA than IgM and remarkable persistence of IgG over time [ 39 41 ]. We previously described the kinetics of anti-N IgM and anti-S IgG antibody responses up to 3 months after natural infection using a commercial Euroimmun ELISA [ 42 ]. In this study, we used several serological assays to measure IgA and IgM antibodies levels against the nucleocapsid protein (NCP) at 1 month after symptom onset, and monitored IgG against the RBD in the S1 subunit and anti-N IgG up to 1 year after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Seropositivity to anti-SARS-CoV-2 antibodies was used as a biomarker of exposure to the SARS-CoV-2 virus. IgM class immunoglobulins were used as a marker of recent or current infection (usually from days 5-7 after symptoms appear, but sometimes later and decrease at days 15-22), and IgG class immunoglobulins were used as a biomarker of older infection (detectable from day 11 post symptom, reaching a maximum 3-4 weeks after and persist days 90 after) [29, 30]. Serological tests were performed by qualitative ELISA for IgM and quantitative ELISA for IgG following the instructions for the WANTAI SARS-CoV-2 IgM ELISA (Beijing Wantai Biological Pharmacy Enterprise, Beijing, China; Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Seropositivity to anti-SARS-CoV-2 antibodies was used as a biomarker of exposure to the SARS-CoV-2 virus. IgM class immunoglobulins were used as a marker of recent or current infection (usually from days 5-7 after symptoms appear, but sometimes later and decrease at days [15][16][17][18][19][20][21][22], and IgG class immunoglobulins were used as a biomarker of older infection (detectable from day 11 post symptom, reaching a maximum 3-4 weeks after and persist days 90 after) [29,30]. recommended by the WHO for seroepidemiological studies, which detects total antibodies (including IgM and IgG) binding the SARS-CoV-2 spike protein receptor binding domain (S1/RBD) [31].…”
Section: Blood Collection and Sars-cov-2 Antibodies Detectionmentioning
confidence: 99%